2020
DOI: 10.1177/0194599820941012
|View full text |Cite
|
Sign up to set email alerts
|

Disease‐Specific Quality of Life in Vestibular Schwannoma: A National Cross‐sectional Study Comparing Microsurgery, Radiosurgery, and Observation

Abstract: Objective To examine the impact of treatment on disease-specific health-related quality of life (HRQOL) among patients with sporadic vestibular schwannoma (VS). Study Design National cross-sectional study. Setting Tertiary referral center and the Acoustic Neuroma Association. Subjects and Methods Adult patients with VS who completed the Penn Acoustic Neuroma Quality of Life (PANQOL) survey. Patients were classified by treatment at the most recent survey as microsurgery, radiosurgery, observation, or recently d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…On top of that, 71% of the patients reported to have received active treatment in our study while a large population-based study by Reznitsky et al shows that 48.4% of 3637 patients were actively treated during a mean 7.33 years of follow-up [ 45 ], limiting the generalizability of our results. However, when looking at questionnaire studies in the field of VS, actively treated patients tend to respond more to surveys (70.3–72.5%), comparable to our findings [ 3 , 27 , 46 ]. Yet patients who were actively treated might have had larger tumours upfront with more complaints and a higher burden, though there is a limited relation with tumour size or growth and for example hearing loss [ 47 ].…”
Section: Discussionsupporting
confidence: 90%
“…On top of that, 71% of the patients reported to have received active treatment in our study while a large population-based study by Reznitsky et al shows that 48.4% of 3637 patients were actively treated during a mean 7.33 years of follow-up [ 45 ], limiting the generalizability of our results. However, when looking at questionnaire studies in the field of VS, actively treated patients tend to respond more to surveys (70.3–72.5%), comparable to our findings [ 3 , 27 , 46 ]. Yet patients who were actively treated might have had larger tumours upfront with more complaints and a higher burden, though there is a limited relation with tumour size or growth and for example hearing loss [ 47 ].…”
Section: Discussionsupporting
confidence: 90%
“…While most studies utilizing PANQOL have assessed how treatment modality impacts QOL in patients with VS, 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 we sought to determine the specific baseline characteristics and surgical outcomes that influence the QOL of patients who undergo microsurgical resection. Expectedly, we identified that functional outcomes, such as hearing preservation and HB grade, had a significant impact on self-reported scores within the hearing and facial domains.…”
Section: Discussionmentioning
confidence: 99%
“…The PANQOL questionnaire has been applied in several studies analyzing QOL outcomes in patients between different VS treatment groups, such as microsurgery, stereotactic radiosurgery, and observation, and authors have suggested various factors that influence patient QOL. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 Here, we utilize the PANQOL questionnaire in patients who elected to receive microsurgical resection of VS to determine the baseline and surgical characteristics that most significantly impact QOL outcomes. The present study not only analyzes QOL outcomes in a large microsurgical cohort, but also provides analysis of how facial and hearing preservation, extent of resection, and retreatment vary in their association with QOL outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of VS, as opposed to treatment modality chosen, seems to have the biggest impact on the quality of life. 21 22 Symptoms most influential on lowering quality of life were ongoing headaches and dizziness with facial nerve function and hearing loss less siginficant. 23 Patients experience improved quality of life following GTR as compared with having residual tumor.…”
Section: Discussionmentioning
confidence: 99%